Der Weg zu einer zukunftsfähigen Familienpolitik - Jutta Allmendinger; Michelle Boden (Wirtschaftsdienst, 2023)
– Before the 2023 summer recess, family policy was, surprisingly, the centre of political debate. Guaranteed child allowance, the abolition of parental benefits for the highest earners, the abolition of income tax relief for married couples, and the pension for surviving dependents were up for negotiation. However, the heated discussions neglected the central question: In which direction is our society headed, and what must our family policy aim for? What criteria should it follow? This article addresses these questions, outlines the situation of children and parents, sketches normative guidelines for an inclusive family policy and makes suggestions for its design.
Keywords: J13; H53; I24; 330; Familienpolitik; Zukunft; Deutschland; Familienpolitik; Zukunft; Deutschland